Attitude control of micro-satellites - Chu, Yun Chung. (2008)
This report summarizes the research work carried out in the AcRF project RG 9/00 Attitude Control of Micro-Satellites in the period of December 2000-December 2004. The research work has focused on the optimal, adaptive, and robust attitude control of micro-satellites under external disturbances and uncertainties in inertia matrix. Using the unit quaternion to represent the attitude of spacecraft and applying the concept of extended disturbances, we have addressed the attitude tracking control problem wim external disturbances via the inverse optimal control method. It is shown in this report that by means of a Lyapunov argument, the proposed attitude controller is optimal with respect to a meaningful cost functional and achieves Hx disturbance attenuation without solving the associated Hamilton-Jacobi-Isaacs partial differential equation explicitly. Based on the analysis in terms of performance limitation, guidelines for the selection of the controller gains are also given. The results are illustrated with numerical simulations.